Problemas relacionados ao viver com diagnóstico do Diabetes Mellitus - CAVALCANTE, Marcos Ronad Mota (2018)
Introduction: Diabetes mellitus (DM) is a metabolic syndrome of multiple origin caused by the lack of insulin secretion or its inability to act, and it evolves slowly and progressively. Their treatment involves changes in lifestyle and use of medications. The increase in its prevalence is characterized as an epidemic. Objective: To evaluate Living Related Problems with the diagnosis of Diabetes Mellitus in users followed at University Hospital - Presidente Dutra Unit (HUUPD). Methodology: A crosssectional, analytical study carried out from September 2017 to March 2018. Two questionnaires were applied, one evaluated the socioeconomic, demographic and clinical factors, and the other the Brazilian Version of Problem Areas in Diabetes (B - PAID), to assess the problems arising from the disease. The statistic was performed using measures of absolute frequency, percentages, means and standard deviation, the Chi-square test analyzed the association between emotional distress and exposure variables, the Lilliefors test assessed the normality of the distribution of the variables. The B-PAID dimensions were compared between the categories of the exposure variables using the Mann-Whitney or Kruskal-Wallis tests. Pearson's correlation coefficient estimated the correlation between B-PAID dimensions and numerical exposure variables. Results: Were studied 308 DM carriers. There was predominance of females (68.5%), over 60 years (54.8%), married or in stable union (48.4%), schooling (51%) and income (65.3%), color / brown race (48.4%), retirees (46.4%). The largest type II (76.6%) group, treated (95.8%), diagnosed for more than 5 years (33, 8%), did not monitor capillary glycemia (88.3%), used medications (94.2%), physical activity (56.8%), 41.6% ex-smoker and ex-smoker. In B-PAID, 25.3% presented emotional distress (B-PAID≥40) and the sub-dimension that contributed the most was emotional problems. Statistically significant associations with emotional distress, gender, marital status, age, race/color, education, income origin, treatment, medications and smoking. In the analysis of the 4 sub-dimensions we had: emotional problems more frequent in indigenous, married / stable union and smokers. Problems with treatment: men, indigenous, from the capital and smokers. Problems with feeding: men, indigenous, married / stable union, from the capital, do treatment, use medication and smokers. Problems with social support: significant in indigenous, from the capital and smokers. Age, schooling and income showed a correlation with B-PAID dimensions. Conclusion: It is concluded that emotional problems are the ones that contribute most to emotional suffering and that this is more present in men, younger and married patients / stable union, indigenous people of the capital and with average income and schooling. Performing treatment, making use of medication and smoking are factors that are associated with the suffering of patients. According to the dimensions of the B-PAID scale, emotional problems were significant in the indigenous, married / stable union and smokers. Problems with treatment in men, indigenous, from the capital and smokers. Significant feeding problems in men, indigenous, married / stable union, from the capital, in treatment and use of medications and smokers. Already the problems with social support were relevant in the indigenous, from the capital and smokers.